The Influence of Education and Local Culture on Community Preparedness in Facing Disasters - Sayuti, Rosiady Husaenie; Inderasari, Oryza Pneumatica; Evendi, Azhari (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
This research is motivated by the awareness of the importance of community preparedness against disasters, especially for island communities whose locations are in disaster-prone areas. Maringkik Island, East Lombok Regency was chosen as the research location because the island is included in the southern part of Lombok Island which has the potential for megathrust with earthquakes above 8 SR. The objectives of this study were to determine: (1) the level of community education in Maringkik Island and its effect on community readiness in dealing with current disasters, (2) the level of understanding of disaster preparedness in the community in patron-client relationships, and (3) the level of disaster preparedness in the local social system of community in Maringkik Island, East Lombok Regency. The method used in this research is mixed methods, a combination of quantitative and qualitative research. The data were collected using in-depth interviews and surveys using a questionnaire that had been prepared. The results obtained from this study are that community preparedness in facing disasters is influenced by several factors, namely the level of education and knowledge as well as existing socio-cultural values. In addition, the existing patron-client pattern actually contributes to the community's low understanding of disaster preparedness. Community behavior and preparedness in the event of a disaster are still traditional, instinctive and natural, not based on modern science. Therefore, this study recommends the importance of disaster-specific subjects in schools and routine disaster mitigation-related training from related institutions.